Duração razoável do processo - Mendes, Iratelma Cristiane Martins (2008)
The subject approached is contemporary and is of great relevance to the society, which distinguishes itself and longs for justice application. However, this anxiety is not based on yesterday´s justice, but on today´s. The Human Rights evolution is analyzed with focus on the reasonable process length, norms of fundamental marks as introduced on the Political Letter of 1988. It analyzes the principles which are applicable to the process, the basis and usage as source of right and material for appreciation and surrender of jurisdictional tutelage to the concrete case. It demonstrates that the process is not the aim itself, and that the legislator has been progressively introducing norms, which are applicable to the private relations, the true tools which are effective and fast, conflict pacifiers. The society claims for the jurisdictional action and justice effectiveness and the Judiciary Power has to follow up the advancements and social changes. For that, the State responsibility shall be evaluated, when it does not provide with proper ways to the fundamental right of reasonable length. It is developed in conformity with the neo-positivism lecturing on the new Legislative structure, which proposes the stimulus of human being dignity and the Justice distribution. At last, the main points which have motivated such insertion of the reasonable process time shall be approached under the scope of fundamental rights and effective tools in search of urgent tutelage and emergency as applicable to the labor process